Selective Removal of Necrotic Dentin in Primary Teeth Using Laser Irradiation: One-Year Clinical Evaluation of Composite Restorations - Polizeli, Silvana Aparecida Fernades; Curylofo-Zotti, Fabiana Ameida; Valério, Rodrigo Alexandre; Nemezio, Mariana Alencar; Souza-Gabriel, Aline Evangelista; Borsatto, Maria Cristina; Corona, Silmara Aparecida Milori (Journal of Lasers in Medical Sciences, 2019)
Introduction: This study aimed to evaluate the child’s salivary cortisol levels, clinical performance and marginal adaptation of restorations after selective removal of necrotic dentin in primary teeth using Er: YAG laser irradiation. Methods: A double-blind clinical study was performed in children at 7-10 years. Children who had at least 2 teeth with carious lesions involving the occlusal and proximal surfaces of primary molars counterparts were selected. Removal of necrotic dentin was performed by 2 methods: Er: YAG laser irradiation and bur-preparation. Cortisol levels (n = 24) was evaluated by ELISA. Clinical analysis (n = 20) was performed after the restorations polish, 6 and 12 months after restorative procedure using United States Public Health Service (USPHS) method and photographs. Scanning electron microscopy (SEM) was used to analyz the marginal gap formation (n = 20). The analysis of the data was performed by 95% confidence interval, Shapiro-Wilk test, Friedman and Wilcoxon post hoc tests (α = 5%). Results: Cortisol levels were higher during selective removal of necrotic dentin, regardless of the method used (P > 0.05). After 12 months, there was no evidence of the difference in the restorations performed on cavities prepared by both methods. SEM analysis revealed that the laser-irradiated teeth showed 10% of gaps in the full extent of restoration. For bur-prepared teeth, 20% of gaps were found at the cavosurface margin. Conclusion: The salivary cortisol levels on children that received Er: YAG laser irradiation for removal the necrotic dentin was similar to the control group. Class II restorations evaluated after 1 year period did not suffer interference by the use of Er: YAG laser irradiation.